THE FUSION OF MEDICINE AND E-COMMERCE: CRAFTING INTEGRATED MARKETING SOLUTIONS FOR THE FUTURE (International Journal of Food and Nutritional Sciences, 2021)
Technology has grown to play a significant role in our daily lives. The use of digital marketing has beenexpanding across all industries. Unfortunately, the pharmaceutical business has not yet mastered digitalmarketing outside the Internet. As part of their broader marketing plan, some companies are attempting tograsp digital's real worth, while others are incorporating it. To understand why, even if retail pharmaciesare still there, more and more individuals are opting to purchase healthcare items and medications online,this article examines the role of digital marketing in this sector. According to the results of this research,digital marketing is here to stay, and digital direct marketing, discounts/offers, and the like are drivingconsumers to purchase healthcare items and medications online.